Local control of S atoms on the Co-SACs for effective activation of PMS and degradation imidacloprid: Mechanism insights and toxicity evaluation - Zehua Wang; JiaoXue Yang; Guochun Lv; Xiaomin Sun; Hongjie Wang (Ecotoxicology and Environmental Safety)
Imidacloprid (IMI), as an emerging pollutant, is frequently detected in pesticide wastewater. Cobalt-based single-atom catalysts (Co-SACs) doped with sulfur atoms can serve as an efficient strategy to activate peroxymonosulfate (PMS) and degrade organic pollutants. The paper employed density functional theory and computational toxicology to deeply explore the mechanism and ecotoxicity of IMI when S atoms were introduced into Co-SACs for PMS activation. The result demonstrated that PMS can be preferentially decomposed into SO4•-, HO•, and 1O2 based on Co-S4-C0 active-center. It exhibited the most positive charge (+0.91 e-), highest electron transfer (0.84 e-), most negative adsorption energy (Eads = −53.85 kcal/mol), and longer O-O bond (1.48 Å). In the degradation processes of IMI, HO•-addition at the C2 sites and HO•-abstract at the H6 sites had the lowest Gibbs free barrier with 6.64 kcal/mol and 6.22 kcal/mol, respectively. Hydroxylation products were readily formed. Route 3 and 7 were the formation pathways of important experimental intermediates (PC3–4). Eco-toxicity assessment showed that most degradation products were completely harmless to aquatic toxicity. PC1–2, PC1–2, PC3–1, PC3–3, PC4–1 and PC4–2 showed similar and higher mutagenicity and bioaccumulation factors to the IMI. Therefore, Route 1, 3 and 4 contributed to the potential health risks. This study not only elucidated the atomic level relationship between PMS and Co-SACs, but also contributed to understanding the detailed degradation mechanism of IMI and the ecotoxicity of TPs. The finding provides theoretical support for environmental impacts of pesticide wastewater during advanced oxidation treatments.